Mapping university receptor patents based on claim-embodiment quantitative analysis: A study of 31 cases from the University of Tokyo. (September 2016) - He, Jihong; Yamanaka, Takayuki; Kano, Shingo
Abstract: This study aimed to develop a quantitative method that is capable of mapping university patents by analyzing the contents of the claims and examples provided in patent specifications. First, two scoring parameters related to the claims and the exemplified embodiment were defined to assess the grantability of a patent application. Second, several assumptions were formulated, and a model was constructed based on these assumptions. A collection of 31 university patent applications in the biomedical field were studied in depth to validate the model.